Prostaglandins for inducing labour and abortion. Issue 11 (25th May 1973) - Unknown
Abstract : Prostaglandins (PGs) are a group of biologically active fatty acids widely distributed throughout mammalian tissues. One effect of administered PGs is the induction of uterine contractions and they have therefore been used to induce labour and abortion. Two prostaglandins, dinoprostone (PGE2 ; Prostin E2 - Upjohn) and dinoprost (PGF2α ; Prostin F2α - Upjohn) are now marketed in Britain for use in 'hospitals and clinics with specialised obstetric and gynaecology units'.